Perencanaan Komunikasi Digital Akun Instagram @ASPAN_Lampung: Studi kasus pada akun Instagram PT. ASPAN Lampung - Agistia Nurfadilah Putri Al Mega; Dadi Ahmadi (UNISBA Press, 2022)
Abstract. The development of information and communication technology has brought innovations in communication bringing society into the digital era. Through digital media, public relations can compile, publish, and disseminate general information about the company to the public for positive public opinions to gain a sense of trust. This research entitled